2022
DOI: 10.3389/fnins.2022.925792
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid type-2 receptors: An emerging target for regulating schizophrenia-relevant brain circuits

Abstract: Although the cannabinoid type-2 receptor (CB2) is highly expressed in the immune system, emerging evidence points to CB2 playing a key role in regulating neuronal function in the central nervous system. Recent anatomical studies, combined with electrophysiological studies, indicate that CB2 receptors are expressed in specific dopaminergic and glutamatergic brain circuits that are hyperactive in schizophrenia patients. The ability of CB2 receptors to inhibit dopaminergic and hippocampal circuits, combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 125 publications
0
1
0
Order By: Relevance
“…This belief stemmed from the findings of Munro et al, who, during their cloning of the receptor, failed to locate CB 2 receptor mRNA in any region of the brain [10]. However, many studies have recently shown that CB 2 R plays a functionally relevant role in the central nervous system and various pathologies associated with the brain [34][35][36][37]. The comprehensive understanding of the CB2 receptor's existence and function inside the central nervous system remains inadequate.…”
Section: Cb 2 Receptor: Molecular Characterization and Spatial Distri...mentioning
confidence: 99%
“…This belief stemmed from the findings of Munro et al, who, during their cloning of the receptor, failed to locate CB 2 receptor mRNA in any region of the brain [10]. However, many studies have recently shown that CB 2 R plays a functionally relevant role in the central nervous system and various pathologies associated with the brain [34][35][36][37]. The comprehensive understanding of the CB2 receptor's existence and function inside the central nervous system remains inadequate.…”
Section: Cb 2 Receptor: Molecular Characterization and Spatial Distri...mentioning
confidence: 99%